Educational robotics studies in Italian scientific journals: A systematic review - Bonaiuti, Giovanni; Campitiello, Lucia; Di Tore, Stefano; Marras, Arianna (Frontiers in Education, 2022)
In recent years, there has been increasing attention to applying educational robotics (ER) in learning settings and, consequently, it has concerned and involved the entire pedagogical field, giving rise to a large amount of experimentation and research. Educational robots are used within the school curriculum and in extra-curricular activities to improve student interest, engagement and academic achievement in various fields, such as STEM and digital literacy, and in many other ways, for example fostering specific cognitive and socio-relational skills. In Italy, as in many other countries, an increasing number of publications are featuring this subject. While there are also some reviews, none of them has been interested in reviewing studies published in Italian journals. The aim of this work is to provide a systematic review of the literature regarding studies investigating educational robotics and provide suggestions for further research and teaching practices. To do this we used the PRISMA statement process. In total, 28 studies published between 2011 and 2021 in 49 Italian journals were analyzed. The main findings from this review provide the current state of the art on research in ER. Furthermore, the paper discusses trends and the vision towards the future and opportunities for further research.